2015
DOI: 10.3389/fphys.2015.00319
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption: an actor of dental and periodontal development?

Abstract: Dental and periodontal tissue development is a complex process involving various cell-types. A finely orchestrated network of communications between these cells is implicated. During early development, communications between cells from the oral epithelium and the underlying mesenchyme govern the dental morphogenesis with successive bud, cap and bell stages. Later, interactions between epithelial and mesenchymal cells occur during dental root elongation. Root elongation and tooth eruption require resorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Both root elongation and tooth eruption require resorption of surrounding alveolar bone 6 . Eventually, majority of epithelial tissue is lost when teeth erupt into oral cavity and reach final length.…”
Section: Tooth Development and Dental Stem Cellsmentioning
confidence: 99%
“…Both root elongation and tooth eruption require resorption of surrounding alveolar bone 6 . Eventually, majority of epithelial tissue is lost when teeth erupt into oral cavity and reach final length.…”
Section: Tooth Development and Dental Stem Cellsmentioning
confidence: 99%
“…OPG is a soluble protein that can bind to RANKL with high affinity and compete with RANK, so it acts as an inhibitor of the RANKL effect on osteoclastogenesis [10]. Studies have demonstrated the direct involvement of RANKL/RANK/OPG signaling in the morphogenesis of the craniofacial skeleton and its growth, including control of the alveolar bone remodeling necessary for tooth growth and eruption [11][12][13]. Interestingly, in mice, RANK overexpression in the monocyte/macrophage lineage (Rank Tg ) induces increased osteoclastic activity and premature dental eruption, while partial RANKL invalidation (Rankl +/-) induces decreased osteoclastic activity and a delay in dental eruption [14].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic mechanisms such as an Opg/Rank/Rankl feedback loop (Ohazama et al, 2004;Alfaqeeh et al, 2013) that regulate osteoclast activity at the interface of the developing M3 (e.g., Wise et al, 2011;Ge et al, 2015) may also contribute to impaction. In mouse models, higher osteoclast number and activity coincide with larger molar size, accelerated molar root formation, and earlier molar eruption (Castaneda et al, 2011;Alfaqeeh et al, 2013), suggesting that signals (e.g., RANK-RANKL) from bone are integral to timely, proportionate molar development (Gama et al, 2015). Thus, M3 impaction may be a product of improper signaling resulting in off-balanced local alveolar bone deposition and resorption.…”
Section: At the Edges Of Spacementioning
confidence: 99%